2010
DOI: 10.2478/v10173-010-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Computer cooling using a two phase minichannel thermosyphon loop heated from horizontal and vertical sides and cooled from vertical side

Abstract: In the present paper it is proposed to consider the computer cooling capacity using the thermosyphon loop. A closed thermosyphon loop consists of combined two heaters and a cooler connected to each other by tubes. The first heater may be a CPU processor located on the motherboard of the personal computer. The second heater may be a chip of a graphic card placed perpendicular to the motherboard of personal computer. The cooler can be placed above the heaters on the computer chassis. The thermosyphon cooling sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The generalized model of the two-phase thermosyphon loop and its different variants were demonstrated in previous papers [2,[6][7][8][9][10][11][12]. This paper presents the theoretical analysis and the experimental data obtained for a new designed variant particularly suited for computer cooling requirements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generalized model of the two-phase thermosyphon loop and its different variants were demonstrated in previous papers [2,[6][7][8][9][10][11][12]. This paper presents the theoretical analysis and the experimental data obtained for a new designed variant particularly suited for computer cooling requirements.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the heat sources can be sitted at the bottom horizontal pipe or on the right/left vertical channels; similarly, the heat sinks can be chosen at the top horizontal pipe or on the right/left verti-cal channels. It is shown that this generalized model can be used to describe any possible individual variants of thermosyphon loop including the earlier variants developed by the author [2,[8][9][10][11][12]. Fluid flow in a thermosyphon loop is created by the buoyancy force that evolves from the density gradients induced by temperature differences in the heating and cooling sections of the loop.…”
Section: The Generalized Model Of Two-phase Thermosyphon Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-dimensional, steady-state governing equations for thermosyphon loop with minichannels and minipump can be written as [3][4][5][6][7][8][9][10]18]:…”
Section: Governing Equationsmentioning
confidence: 99%
“…The total length of the loop is denoted by L, the cross-section area of the channel by A and the wetted perimeter by U . Both superheating and subcooling are neglected and a linearly varying quality function x(s) are assumed according to [3][4][5][6][7][8][9][10].…”
Section: The Model Of the Two-phase Thermosyphon Loop With Minichannementioning
confidence: 99%